Family Disharmony as a Reason for Divorce (Analysis of Religious Court Decision in Medan 2017, Psychology and Sociology Perspective) - Mustapa Khamal Rokan; Imam Yazid; Bagus Ramadi (Budapest International Research and Critics University, 2020)
Family harmony becomes a strong foundation in upholding the integrity of the household, on the other hand, family disharmony is the cause of the collapse of family buildings that have been successfully cultivated. In the last two years, from 2016-2017 the number of divorce cases due to family disharmony has increased significantly. More divorce suits were filed by wives than husbands. This study looks at the problems that occur with the juridical-analysis approach to see the legal facts of the reasons for divorce and to analyze the factors that cause family disharmony based on the decisions analyzed and the research data obtained in the field. Based on the analysis that the author did and saw the facts that the disharmony occurred, it was the culmination of various family problems that the spouses were unable to resolve properly, resulting in continuous disputes that ended in divorce. The paradigm of divorce today is much different from the previous conditions. In the past, divorce was a bad disgrace, divorce was considered a failure in building a family and divorce actors received social sanctions in society.